The Twits - Roald Dahl (New York, NY, United Kingdom Penguin Books Ltd, 2011)
The Twits are possibly the nastiest and most digusting of all Roald Dahl's characters.Frogs in beds; Eyeballs in drinks; Worms in spaghettiMr and Mrs Twit are really disgusting. They smell because they never wash, they fight because they play tricks on each other, AND they hate children. But worst of all, they keep monkeys in their back garden. In cages. It's time for the monkeys to get their revenge on these two most revolting creatures . . . ***meet the Muggle-Wump monkeys and the Roly-Poly bird!******with a great new cover by Quentin Blake, and a whole exciting section about Roald Dahl and his world***'A true genius . . . Roald Dahl is my hero' - David WalliamsRoald Dahl, the best-loved of children's writers, was born in Wales of Norwegian parents. After school in England he went to work for Shell in Africa. He began to write after "a monumental bash on the head", sustained as an RAF pilot in World War II. Roald Dahl died in 1990.Quentin Blake is one of the best-known and best-loved children's illustrators and it's impossible now to think of Roald Dahl's writings without imagining Quentin Blake's illustrations.
Kate Greenaway Medal
Keywords: Fantasy -- Fantasy